Fluctuations of Histone Chemical Modifications in Breast, Prostate, and Colorectal Cancer: An Implication of Phytochemicals as Defenders of Chromatin Equilibrium - Marek Samec (14727823) (2019)
Natural substances of plant origin exert health beneficiary efficacy due to the content of various phytochemicals. Significant anticancer abilities of natural compounds are mediated via various processes such as regulation of a cell’s epigenome. The potential antineoplastic activity of plant natural substances mediated by their action on posttranslational histone modifications (PHMs) is currently a highly evaluated area of cancer research. PHMs play an important role in maintaining chromatin structure and regulating gene expression. Aberrations in PHMs are directly linked to the process of carcinogenesis in cancer such as breast (BC), prostate (PC), and colorectal (CRC) cancer, common malignant diseases in terms of incidence and mortality among both men and women. This review summarizes the effects of plant phytochemicals (isolated or mixtures) on cancer-associated PHMs (mainly modulation of acetylation and methylation) resulting in alterations of chromatin structure that are related to the regulation of transcription activity of specific oncogenes, which are crucial in the development of BC, PC, and CRC. Significant effectiveness of natural compounds in the modulation of aberrant PHMs were confirmed by a number of in vitro or in vivo studies in preclinical cancer research. However, evidence concerning PHMs-modulating abilities of plant-based natural substances in clinical trials is insufficient. Other Information Published in: Biomolecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/biom9120829